Resources and Destination Competitiveness Factors Important for Planning Sport Tourism Supply - Ivan Novak (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The aim of this paper is to determine resources and competitive factors of sport tourism suitable to Croatian tourism business circumstances. There are numerous researches on similar topics. However, for this paper and according to accessible and processed sources, had not been found research that determine and treats concept of sport comprehensively, by the sub-areas of sport. Sport tourism in theory represents a selective form of tourism and should be based, in accordance with contemporary trends, on comparative competitiveness and sustainable development. Sustainable development includes a wide range of relevant platforms that are essential for sustainable planning. These platforms influence the sustainable planning of sport tourism supply. The question is what are the resources and factors that are important for the planning of sport-tourism supply and fit into comparative competitiveness and sustainable development? The practical and theoretical purpose of work are manifested through the determination of resources and factors important for the planning and development of sport tourism in those destinations that want to develop this form of selective tourism. In these destinations such created supply of sports and recreational amenities and facilities should resulted with increase in consumption. Previously defined resources and factors should be the basis for the planning of the overall development of a particular destination and, consequently, for decision-making process on potential investment engagements. Such structural changes should also reflected on the structure of the supply and potentially define changes in the guests structure/profile and their demand or consumption. Thus, in this paper determined resources and factors, if applied, should affect directly or indirectly the planning and decisions development in each particular destination.
Keywords: 650; selective tourism; sports tourism; resources; competitive factors; impacts